Association of BDNF gene polymorphism with endophenotypes in posttraumatic stress disorder - Guo,Jun-Cheng (2020)
SUMMARY OBJECTIVE To explore the association of brain-derived neurotrophic factor gene (BDNF) polymorphism with the latent cognitive endophenotype of posttraumatic stress disorder (PTSD) after major natural disasters in Hainan Province, China. METHODS A total of 300 patients with PTSD and 150 healthy controls (HC) were surveyed by psychoanalysis scale to assess their cognitive functions. Polymerase chain reaction (PCR) and polyacrylamide gel electrophoresis (PAGE) were used to detect the BDNF gene polymorphism. RESULTS In terms of the cognitive function, the scores in the PTSD group were worse than those of the HC group (P < 0.05 or P < 0.01). There was a significant difference in the distribution of BDNF genotype and allele frequency between the two groups (P < 0.05). PTSD endophenotypes were significantly different among the BDNF genotypes in the PTSD group (P ≤ 0.01). CONCLUSION There is a statistically significant difference in the polymorphism of BDNF gene between PTSD and HC groups, and the alleles are associated with the incidence of PTSD. Thus, it may be a risk factor for PTSD.